(untitled) (Annals of Medical Research, 2025)
Aim: This study aimed to morphometrically examine the posterior tibial curvature (PTC) on the sagittal plane in the proximal and distal tibia regions. Materials and Methods: Forty-eight (21 right, 27 left) dry tibia bones were used. Both linear and angular parameters were measured on ImageJ. Linear measurements: Tibiae were placed on a horizontal surface on their posterior face. Tibiae were photographed from the medial aspect. In the photographs, the distance between the proximal and distal contact points (proximal: C0P, distal: C0D) of the tibia with the horizontal plane was divided into eight equal parts by 7 (C1- C7) landmarks. From each landmark to the tibia, perpendiculars were drawn. The intersections of the perpendiculars with the posterior margin of the tibia were determined (C1’-C7’). The distances between corresponding landmarks were measured (H1-H7). The heights of the tibiae (L) were also measured. Angular measurements: Lines were drawn between each landmark on the proximal tibia and the proximal contact point of the tibia (C0P) for A1 to A3. Similarly, lines were drawn between each landmark on the distal tibia and the distal contact point of the tibia (C0D) for A5 to A7. Angles between these lines and horizontal lines measured (A1-A7). Results: There were no statistically significant differences between right and left for all parameters. H1, H2 and H3 were statistically greater than the H7, H6 and H5, respectively. A1, A2 and A3 were statistically greater than the A7, A6 and A5, respectively. Sagittal distances and angles in the proximal region were observed to be higher than the distal region. Conclusion: Tibial morphometry is crucial for treating tibial fractures, planning regional surgeries, assessing surgical outcomes, and preventing complications. We hope that the method proposed in this study will be preferred for evaluating the morphometric characteristics of the posterior curvature of the tibia, particularly in the context of tibial biomechanics or personalized surgical planning.